Focal point determination in magnetic resonance‐guided focused ultrasound using tracking coils. Issue 6 (15th July 2016) - Svedin, Bryant T.; Beck, Michael J.; Hadley, J. Rock; Merrill, Robb; de Bever, Joshua T.; Bolster, Bradley D.; Payne, Allison; Parker, Dennis L.
Abstract : Purpose: To develop a method for rapid prediction of the geometric focus location in MR coordinates of a focused ultrasound (US) transducer with arbitrary position and orientation without sonicating. Methods: Three small tracker coil circuits were designed, constructed, attached to the transducer housing of a breast‐specific MR‐guided focused US (MRgFUS) system with 5 degrees of freedom, and connected to receiver channel inputs of an MRI scanner. A one‐dimensional sequence applied in three orthogonal directions determined the position of each tracker, which was then corrected for gradient nonlinearity. In a calibration step, low‐level heating located the US focus in one transducer position orientation where the tracker positions were also known. Subsequent US focus locations were determined from the isometric transformation of the trackers. The accuracy of this method was verified by comparing the tracking coil predictions to thermal center of mass calculated using MR thermometry data acquired at 16 different transducer positions for MRgFUS sonications in a homogeneous gelatin phantom. Results: The tracker coil predicted focus was an average distance of 2.1 ± 1.1 mm from the thermal center of mass. The one‐dimensional locator sequence and prediction calculations took less than 1 s to perform. Conclusion: This technique accurately predicts the geometric focus for a transducer with arbitrary position and orientation without sonicating. Magn Reson Med 77:2424–2430, 2017. © 2016 International Society for Magnetic Resonance in Medicine